IVIg attenuates complement and improves spinal cord injury outcomes in mice. Issue 7 (25th May 2016) - Brennan, Faith H.; Kurniawan, Nyoman D.; Vukovic, Jana; Bartlett, Perry F.; Käsermann, Fabian; Arumugam, Thiruma V.; Basta, Milan; Ruitenberg, Marc J.
Abstract: Objective: Traumatic spinal cord injury (SCI) elicits immediate neural cell death, axonal damage, and disruption of the blood–spinal cord barrier, allowing circulating immune cells and blood proteins into the spinal parenchyma. The inflammatory response to SCI involves robust complement system activation, which contributes to secondary injury and impairs neurological recovery. This study aimed to determine whether intravenous immunoglobulin (IVIg), an FDA‐approved treatment for inflammatory conditions, can scavenge complement activation products and improve recovery from contusive SCI. Methods: We used functional testing, noninvasive imaging, and detailed postmortem analysis to assess whether IVIg therapy is effective in a mouse model of severe contusive SCI. Results: IVIg therapy at doses of 0.5–2 g/kg improved the functional and histopathological outcomes from SCI, conferring protection against lesion enlargement, demyelination, central canal dilation, and axonal degeneration. The benefits of IVIg were detectable through noninvasive diffusion tensor imaging (DTI), with IVIg treatment counteracting the progressive SCI‐induced increase in radial diffusivity (RD) in white matter. Diffusion indices significantly correlated with the functional performance of individual mice and accurately predicted the degree of myelin preservation. Further experiments revealed that IVIg therapy reduced the presence of complement activation products and phagocytically active macrophages at the lesion site, providing insight as to its mechanisms of action. Interpretation: Our findings highlight the potential of using IVIg as an immunomodulatory treatment for SCI, and the value of DTI to assess tissue damage and screen for the efficacy of candidate intervention strategies in preclinical models of SCI, both quantitatively and noninvasively.